2014
DOI: 10.2320/matertrans.i-m2014808
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Grain Size in Deep Drawing Steel Sheet by Laser Ultrasonics

Abstract: The laser ultrasonic technique has been used to determine grain sizes in Interstitial Free (IF) steels. With an analysis method that employs scattering theory, absolute values of the average grain size have been calculated directly from the ultrasonic traces. These results indicate that the laser ultrasonic technique may be incorporated on-line for direct measurements of grain size during steel production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many researchers have used laser ultrasound to characterize the grain size of metal materials or studied the corrosion resistance of metal materials through grain size. Yin [16] used the analytical method of scattering theory to calculate the absolute value of the average grain size directly from the ultrasonic trajectory. Bai [17] found that there was an approximately linear relation between the centroid frequency ratio of the two successive echoes and the mean grain size was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have used laser ultrasound to characterize the grain size of metal materials or studied the corrosion resistance of metal materials through grain size. Yin [16] used the analytical method of scattering theory to calculate the absolute value of the average grain size directly from the ultrasonic trajectory. Bai [17] found that there was an approximately linear relation between the centroid frequency ratio of the two successive echoes and the mean grain size was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas Garcin [11] used ultrasonic attenuation to evaluate the grain size of Inconel 718 alloy which grew abnormally during the process of Solid solution. Yin AM, He Fei [12,13]and others calculation attenuation of ultrasonic energy to evaluate the grain size of low carbon steel. In order to improve the accuracy of detection, Li Xiongbin [14] and others proposed to use multi-scale ultrasonic attenuation coe cient to evaluate the mean grain size of 304stainless steel, and effectively improve the tting accuracy.…”
Section: Introductionmentioning
confidence: 99%